LIGAND BASED PHARMACOPHORIC DISCOVERY OF NEW CLK1 INHIBITORS: LIGAND BASED PHARMACOPHORIC DISCOVERY OF NEW CLK1 INHIBITORS (Indian Journal of Chemistry (IJC), 2025)
CLK1 has been recognized as an optimistic target against an array of diseases, including cancer due to their pre-mRNA splicing function. In this study, Ligand-based pharmacophore approach has been employed to identify new CLK1 inhibitors from Kinase and FDA approved drug libraries. Two ligands, K6 and D1 were extracted, which established consistent interactions with hinge residues while maintaining a web of interactions in DFG region. Additionally, their stable protein dynamics comparable with reference CLK1 inhibitor (T24) and Apo ratify them as aspiring CLK1 inhibitors. Further, D1, has been identified as a CLK1 binder and K6 as a potential kinase inhibitor by Swiss target prediction server. Moreover, their adequate pharmacokinetic and toxicity profiles make them worth future investigations.